La dimensione formativa dell’interazione con le chatbot AI. Per una pedagogia dialogica digitale - Maria Rita Mancaniello; Francesco Lavanga (Studi sulla Formazione)
Digital dialogic pedagogy embodies an extension of the traditional dialogic, in which digital technologies and, in particular, AI chatbots, take a central role in promoting educational interaction, fostering personalized learning. Question-driven interaction, the foundation of dialogic pedagogy, turns out to be a crucial tool for developing critical thinking and divergent thinking, as well as to stimulate individual autonomy. The interaction between humans and machines evolves from a simple exchange based on preset commands to a deeper dialogue in which AI chatbots are able to stimulate reflections, guide users in formulating questions and personalize feedback based on their individual needs. The concept of digital dialogic pedagogy highlights how artificial intelligence can improve the quality and accessibility of educational dialogue, offering new generative opportunities in diverse learning contexts. Certainly, the educational and scientific worlds are experiencing the value of AI in developing the knowledge and skills of the younger generation, but the integration of AI chatbots into educational practice can not only foster the personalization of learning, but also promotes a more inclusive approach, capable of actively engaging students and learners, regardless of their skills or backgrounds.